(untitled) (Bangladesh Journal of Infectious Diseases, 2024)
Background: Different countries and different regions within those countries have exhibited distinct COVID-19 infection prevalence and clinical outcomes. These are important to assess owing to understanding the magnitude of the disease in a particular area and to initiate appropriate intervention. Objective: The objective of the present study was to investigate the prevalence and outcomes of COVID-19 infection, and its associated sociodemographic factors among the population at the Shylet district in Bangladesh. Methodology: This retrospective study was carried out in the Department of Microbiology at Sylhet MAG Osmani Medical College, Sylhet, Bangladesh from 4 April to 6 September 2020. Patient data collection was collected from different healthcare institutions located in Sylhet. Those patients attended the institutions to diagnose COVID-19 infection during the ongoing pandemic. Microsoft Excel and SPSS software was used for the data analysis. P< 0.05 at a 95.0% confidence interval was specified as the standard of significance. Results: Participants aged more than 60 years old showed the highest rate of death (8.3%) and the lowest proportion of cure (91.7%). A significant association has been found in the COVID-19 infection outcome of the participants with their age, occupation, and place of treatment for infected people (p <0.001*). People aged 20 to 40 years, showed the highest odds of being infected with COVID-19 [OR: 4.685; CI: 1.25 - 17.51; p < 0.05]. Moreover, people taking treatment from private hospitals were significantly less likely [OR: 0.061; CI: 0.03 - 0.13; p < 0.001] to present COVID infection outcomes than those who were treated in public hospitals. Again, healthcare workers had the highest death rate (2.9%) than that of people from other professions. Conclusion: In conclusion, elderly people are commonly died due to COVID-19 infection, which is related to the site of treatment as well as the occupation of the patients. Bangladesh Journal of Infectious Diseases, June 2024;11(1):30-37